Vitamin D, the Cutaneous Barrier, Antimicrobial Peptides and Allergies: Is There a Link? - Roider, Elisabeth (The Korean Academy of Asthma, Allergy and Clinical Immunology; The Korean Academy of Pediatric Allergy and Respiratory Disease, 2013)
Atopic diseases such as atopic dermatitis (AD) are very common in industrialized countries. Up to 15%-30% of all children and 2%-10% of all adults suffer from AD. Already in early disease stages, a defective epidermal barrier is known to contribute to the pathogenesis of AD. Central elements in the epidermal barrier are antimicrobial peptides (AMPs), which are secreted by keratinocytes, sweat gland cells but also infiltrating immune cells. AMPs function as endogenous antibiotics and are able to kill bacteria, viruses, and fungi. Furthermore AMPs act as immune modulators with effects on the innate and adaptive immune system. The probably best studied AMPs in human skin are the defensins and cathelicidin. In atopic diseases the functions of AMPs such as cathelicidin might be impaired and microbial superinfections could serve as cofactors for allergic sensitization. Hence, induction of AMPs could be beneficial in these patients. Cathelicidin which is often referred to its peptide form hCAP18 or LL-37 can be induced by ultraviolet light B (UVB) irradiation and is upregulated in infected and injured skin. The cathelicidin gene carries a vitamin D response element and the vitamin D pathway could therefore be targeted for cathelicidin regulation. As the development and course of atopic diseases might be influenced by vitamin D signaling these pathomechanisms could explain the growing evidence connecting vitamin D to allergic diseases, including AD, allergic rhinitis, food allergies and asthma. In this review the role of vitamin D and the AMP cathelicidin in the pathogenesis of atopic diseases with impaired barrier function will be discussed.